Chemical inhibition of xylem cellular activity impedes the removal of drought-induced embolisms in poplar stems - new insights from micro-CT analysis - Secchi, Francesca (The New phytologist, 2021)
© 2020 The Authors New Phytologist © 2020 New Phytologist Trust.